Chiron elegans, new species from Sub-Saharan Africa (Coleoptera : Scarabaeoidea : Chironidae) - (:unkn) unknown (My University, 2020)
Description and illustration of Chiron elegans n. sp., new species from Sub-Saharan Africa.
Keywords: African Research